Using an abbreviated assessment to identify effective error‐correction procedures for individual learners during discrete‐trial instruction. Issue 3 (19th April 2018) - Carroll, Regina A.; Owsiany, Jennifer; Cheatham, Jessica M.
Abstract : Previous research comparing the effectiveness of error‐correction procedures has involved lengthy assessments that may not be practical in applied settings. We used an abbreviated assessment to compare the effectiveness of five error‐correction procedures for four children with autism spectrum disorder or a developmental delay. During the abbreviated assessment, we sampled participants' responding with each procedure and completed the assessment before participants reached our mastery criterion. Then, we used the results of the abbreviated assessment to predict the most efficient procedure for each participant. Next, we conducted validation assessments, comparing the number of sessions, trials, and time required for participants to master targets with each procedure. Results showed correspondence between the abbreviated assessment and validation assessments for two of four participants and partial correspondence for the other two participants. Findings suggest that a brief assessment may be a useful tool for identifying the most efficient error‐correction procedure for individual learners.